Exploring near-synonymous terms in legal language. A corpus-based, phraseological perspective - Gozdz-Roszkowski, Stanislaw (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
This paper aims to determine the extent to which a corpus-based, phraseological approach can be effectively applied to discriminate among near-synonymous, semantically-related terms which often prove troublesome when translating legal texts. Based on a substantial multi-genre corpus of American legal texts, this study examines the collocational patterns of four legal terms ‘breach’, ‘contravention’, ‘infringement’ and ‘violation’, first in the genre of contracts and then in the multi-genre context of the entire corpus. The findings highlight the area of overlap as well as specificity in the usage of these terms. While collocational constraints can be argued to play an important disambiguating role in the semantic and functional analysis of both source and target text items carried out by translators prior to the interlingual translation, this study emphasizes the applicability of the phraseological approach to English source texts.